Fatigue and recovery in ballet: Exploring the experiences of professional South African ballet dancers - Smith, L. S.; Louw, Q. A.; Brink, Y. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Professional South African ballet dancers face a higher risk of overuse injuries and overtraining syndrome as compared to dancers from other countries; especially towards the end of a ballet season. Fatigue is a major factor leading to overtraining syndrome and injuries in professional ballet dancers. The study aimed to explore the fatigue and recovery experiences of South African ballet dancers, highlighting how they navigate these aspects and the strategies they employ for recovery.